PENGARUH PEMBERIAN APERSEPSI TERHADAP KESIAPAN BELAJAR SISWA PADA PELAJARAN AKUNTANSI KELAS XI SMA ISLAMIYAH PONTIANAK - Al-Muwattho, Fariz Pangestu; Aminuyati, Aminuyati; Okianna, Okianna (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe purpose of this research was to know the influence of apperception by the teachers to students' learning readiness on accounting subjects class XI IPS SMA Islamiyah Pontianak. The method used in this research is a descriptive method with the form of interrelationship studies. This study is a population study with a sample size of 56 students which consists of all students of class XI IPS 1 and XI IPS 2 as respondents. The method used in this research is quantitative descriptive method with the intention of to describe objectively the influence of apperception on students' learning readiness. data processing in this research using correlation technique pearson product moment and coefficient determinant. The conclusion of this research is that the result of calculation coefficient of determination (r2) shows there is significant influence equal to 74% giving apperception by the teacher to readiness of student learning, while 26% other influenced by the other factor. Â Keywords: Apperception, Readiness Learning, Accounting Lessons.